If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + 6 = (a + 4) Reorder the terms: 6 + 9a = (a + 4) Reorder the terms: 6 + 9a = (4 + a) Remove parenthesis around (4 + a) 6 + 9a = 4 + a Solving 6 + 9a = 4 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 6 + 9a + -1a = 4 + a + -1a Combine like terms: 9a + -1a = 8a 6 + 8a = 4 + a + -1a Combine like terms: a + -1a = 0 6 + 8a = 4 + 0 6 + 8a = 4 Add '-6' to each side of the equation. 6 + -6 + 8a = 4 + -6 Combine like terms: 6 + -6 = 0 0 + 8a = 4 + -6 8a = 4 + -6 Combine like terms: 4 + -6 = -2 8a = -2 Divide each side by '8'. a = -0.25 Simplifying a = -0.25
| (x-4)=1 | | 5.8+(-2.5)= | | 3x+3+4x=7x-2+2x+4+7x-2 | | 17=3(p-5) | | 2y+4x=8x+-2 | | 2x/x+4=8/9 | | 2x+7=3x+4 | | 23+4x= | | 52=2x+y | | 7+4x=2x-11 | | 4/5=x/50 | | (2a)/3=-4.54545454545 | | 0.14(y-9)+0.10y=0.4y-0.01(60) | | 10-(-10)-7-5= | | 2c=5c+-19 | | 2(n+9)=3n-5 | | -3(7-4)= | | -3(7-4)= | | 5x+19+74= | | 9-y^2=14x+3 | | 6(9x-8)=47 | | d-17=45 | | -38+3r=8(4r+7)-7 | | 4x-9=7+9x+19 | | -32=-3+7x+3(x-2) | | -5x+7+3x=-1 | | 2(x-3)=5(2x+4) | | b+5=5/11 | | -x-47=31-7x | | 1.2b-1.8=47.4 | | 2a/3+5=5/11 | | 10-(3y-3)=8-4y |